Increased Activated Plasma Cells in Inflammatory Bowel Disease When Compared to Ischemic Acute Colitis. (28th October 2021) - Thorburn, C; Qu, Z; Zhang, P
Abstract: Introduction/Objective: Inflammatory bowel disease (IBD) and acute ischemic colitis can both be involved by active colitis. IBD is characterized by crypt architectural distortion, basal lymphoplasmacytosis, and occasional granulomatous changes. However, diagnosis of IBDs is still largely by exclusion of other types of active colitis with similar changes. We previously demonstrated that glucose regulated protein 94 (grp94) is mainly expressed by activated plasma cells. We postulate that increased numbers of grp94-positive plasma cells may support diagnosis of IBDs. Here, we compared IBD and active ischemic colitis for grp94 expression in mucosal plasma cells of colectomy specimens Methods/Case Report: Tissue sections from colectomy specimens with active IBD (n = 8) and ischemic colitis (n = 7) were examined for grp94 expression by immunohistochemistry (monoclonal antibody clone 9G10 at dilution of 1:200, Enzo Life Science, Inc Farmindale, NY). The staining intensity and highest number of grp94 in plasma cells per high power field was counted and recorded for each case, and combined scores were calculated as # of plasma cells multiplied by staining intensity (ranging from 0 to 3+). Unpaired student T tests were used to compare these indices between the two groups for statistical significance (p value < 0.05 was considered significantly different) Results (if a Case Study enter NA): Plasma cells in lamina propria identified by grp94 staining showed higher intensity in IBD than ischemic groups. The number of plasma cells and combined scores were also significantly higher in the IBC group than that of ischemic group Conclusion: Our data indicates that active plasma cells are much more numerous in IBD than ischemic colitis, supporting the notion that active plasma cells are involved in the development of this disease process. Morphologically, active colitis with increased number of plasma cells appears to be another index favoring the diagnosis of IBD.